Study on the Spatio-Temporal Relationship of Tourism Industry in Jiangxi Province Based on Nighttime Light Remote Sensing Data - Xu, Chenyu; Li, Jinxiang; Cai, Baoyuan (Transactions on Economics, Business and Management Research, 2024)
Nighttime light data serves as a vital indicator reflecting urban economic activities and social vitality, extensively utilized in gauging the level of urban economic development and the status of tourism growth. This study zooms in on 11 prefecture-level cities in Jiangxi Province, collecting data on nighttime light intensity and multifaceted tourism metrics spanning from 2010 to 2020. Following data preprocessing, a Panel Vector Autoregression model is employed, integrated with a multi-step statistical testing approach, to delve into the dynamic relationship between nighttime light and the tourism industry. The findings reveal a positive correlation between nighttime light intensity and both domestic tourist arrivals and domestic tourism revenue. Notably, the number of star-rated hotels exerts a marked influence on nighttime light intensity. Further, through the incorporation of Support Vector Machine modeling, this study explores the differentiated impacts of various tourism indicators on light emissions across time and space. It is discerned that all five indicators examined positively correlate with nighttime light data in Jiangxi’s prefecture-level cities, with star-rated hotels (coefficient = 4.349) and domestic tourism revenue (coefficient = 3.471) exhibiting the most substantial weights, whereas foreign exchange earnings from international tourism exhibit the least influence (coefficient = 0.193). This research quantifies the specific effects of tourism indicators on nighttime light, offering valuable insights for policymakers and night-time economy planners.